GCB-type is a favorable prognostic factor in primary CNS diffuse large B-cell lymphomas. (January 2021) - Marcus, Chelsea; Maragkos, Georgios A.; Alterman, Ron L.; Uhlmann, Erik; Pihan, German; Varma, Hemant
Highlights: The prognostic value of Hans classification (ABC vs GCB) in PCNSL is unclear. Our findings suggest that GCB-type is a good prognostic factor in PCNSL. Older age (>70 years) is a poor prognostic factor in PCNSL. Abstract: Primary CNS lymphomas (PCNSLs) are aggressive diffuse large B-cell lymphomas (DLBCLs) limited to the CNS that generally have a poor prognosis. Classification of DLBCL into germinal center B-cell (GCB) and activated B-cell (non-GCB) subtypes has prognostic value in systemic DLBCL, with GCB-type having a better prognosis. The aim of this study was to determine whether GCB versus non-GCB classification in PCNSLs has similar prognostic value. We analyzed clinical, radiological and histologic data from 24 patients with biopsy confirmed DLBCL of the CNS with classification into GCB versus non-GCB subtypes. We found that after a median follow-up of 15 months, only 39% of patients with non-GCB-type PCNS DLBCL were alive, whereas all patients with GCB-type were alive. Non-GCB-type had a median survival of 11 months, whereas all GCB-type patients were alive after a median follow-up of 22 months. As previously reported, we also found that patients younger than 70 years had longer survival (median 29 months) compared to older patients (median 8.8 months). There was no statistically significant difference between the ages, gender, focality, size or location of lesions, or treatment of non-GCB and GCB-type patients. Our findings suggest that classifying PCNSLs into GCB versus non-GCB subtype using the Hans algorithm may help stratify patients into two groups with different prognosis.